2024
DOI: 10.7150/ijbs.82003
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the HMGB1/RAGE axis protects against cisplatin-induced ototoxicity via suppression of inflammation and oxidative stress

Xiangyun Qiao,
Wen Li,
Zhiwei Zheng
et al.

Abstract: As an anti-tumor drug widely used in the clinic, cisplatin is limited by its ototoxic side effects associated with various factors, including inflammatory responses. Receptor for Advanced Glycation Endproducts (RAGE) recognizes damage-associated molecular patterns (DAMPs) and promotes stress and inflammation. This study intended to determine the potential behavior of the HMGB1/RAGE axis after cisplatin injury and whether it has a protective effect after inhibiting this pathway. We used FPS-ZM1, a RAGE inhibito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 60 publications
0
1
0
Order By: Relevance
“…Another study showed that sevoflurane caused mitochondrial ROS production and elevated cytoplasmic calcium levels, triggering the opening of the mitochondrial permeability transition pore (MPTP) and lowering the mitochondrial membrane potential (MMP), inducing mitochondrial iron overload, and ultimately leading to cognitive dysfunction [ 31 ]. The peripheral auditory nervous system is similarly susceptible to damage by drugs and the environment [ 7 , 32 , 33 ]. Our previous study showed that sevoflurane was capable of producing ototoxicity in the developing peripheral auditory system by inducing oxidative stress [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another study showed that sevoflurane caused mitochondrial ROS production and elevated cytoplasmic calcium levels, triggering the opening of the mitochondrial permeability transition pore (MPTP) and lowering the mitochondrial membrane potential (MMP), inducing mitochondrial iron overload, and ultimately leading to cognitive dysfunction [ 31 ]. The peripheral auditory nervous system is similarly susceptible to damage by drugs and the environment [ 7 , 32 , 33 ]. Our previous study showed that sevoflurane was capable of producing ototoxicity in the developing peripheral auditory system by inducing oxidative stress [ 9 ].…”
Section: Discussionmentioning
confidence: 99%